The LUFS domain, its transcriptional regulator proteins, and drug resistance in the fungal pathogen Candida auris (2019)
The LUFS domain (LUG/LUH, Flo8, single-strand DNA-binding protein [SSBP]) is a well-conserved and apparently ancient region found in diverse proteins and taxa. This domain, which has as its most obvious structural feature a series of three helices, has been identified in transcriptional regulator proteins of animals, plants, and fungi. Recently, in these pages (Wang et al., Protein Sci., 2019, 28:788–793), the first crystal structure of a LUFS domain was reported, for the human SSBP2, a transcriptional repressor. We briefly address how the new insights into LUFS structures might contribute to a better understanding of an important transcriptional activator of yeasts that contains the LUFS domain, Flo8, and consider how a focus on the LUFS domain and its variation could help us to understand etiologies of drug resistance in a recently emerged pathogenic fungus, Candida auris. © 2019 The Protein Society